Nutrient profile of Indian climbing perch, Anabas testudineus (SAARC Journal of Agriculture, 2017)
The proximate composition, fatty acid, amino acid and fat soluble vitamins of Indian climbing perch, Anabas testudineus, locally called Koi were assayed in relation to its body weight. The fish samples were collected from different geographical locations and were grouped as small (10-50g) and big (52-150g) sizes. The proximate composition, essential amino acid (EAA) and non-essential amino acid (NEAA) contents in Koi did not differ significantly between the groups. The monounsaturated fatty acid (MUFA) content was significantly (P